2007
DOI: 10.1152/ajpcell.00030.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 is required for activated pancreatic stellate cells to respond to proinflammatory cytokines

Abstract: Cyclooxygenase-2 (COX-2) mediates various inflammatory responses and is expressed in pancreatic tissue from patients with chronic pancreatitis. To examine the role of COX-2 in chronic pancreatitis, we investigated its participation in regulating functions of pancreatic stellate cells (PSCs), using isolated rat PSCs. COX-2 was expressed in culture-activated PSCs but not in freshly isolated quiescent PSCs. TGF-beta1, IL-1beta, and IL-6 enhanced COX-2 expression in activated PSCs, concomitantly increasing the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 29 publications
3
31
0
1
Order By: Relevance
“…However, key experiments were repeated with primary stellate cells which confirmed the observations. Our studies support the suggestion that HPSCs cells express COX-2 and secrete PGE 2 (22). More importantly, we found that PGE 2 is a powerful regulator of stellate cells that increases their proliferation, migration and the production of extra cellular matrix (ECM) molecules.…”
Section: Introductionsupporting
confidence: 89%
“…However, key experiments were repeated with primary stellate cells which confirmed the observations. Our studies support the suggestion that HPSCs cells express COX-2 and secrete PGE 2 (22). More importantly, we found that PGE 2 is a powerful regulator of stellate cells that increases their proliferation, migration and the production of extra cellular matrix (ECM) molecules.…”
Section: Introductionsupporting
confidence: 89%
“…4). 76 , transforming growth factor-ß (TGFß) 70;77 , interleukin -1 ß (Il-1ß) 78 and epidermal growth factor (EGF) 79 are some of the factors which regulate proliferation, activation, collagen production and apoptosis in the pancreatic stellate cell.…”
Section: Stellate Cells Tumour Stromamentioning
confidence: 99%
“…It has been shown that pancreatic cancer cells are also a source of PSC-activating factors [6][7][8]. The effects of IL-1 and IL-6 on the initiation of PSCs activation might be indirect, through the TGF-b1 production [19]; anti-TGF-b1 neutralizing antibody attenuated a-SMA expression induced by IL-1b and IL-6 [19]. Importantly, PSCs by themselves are capable of synthesizing cytokines, such as TGF-b1, activin A, and IL-1, suggesting the existence of autocrine loops that may contribute to the perpetuation of PSC activation after an initial exogenous signal, thereby promoting the development of pancreatic fibrosis [10][11][12][13].…”
Section: Activation Of Pscsmentioning
confidence: 99%
“…In addition to the Smad-dependent pathway, Smadindependent TGF-b signaling pathways exist, for example, MAP kinases, such as ERK. Thus, TGF-b1 intracellular signaling occurs via Smad-dependent and Smad-independent pathways [19].…”
Section: Janus-activated Kinases (Jak)/signal Transducers and Activatmentioning
confidence: 99%
See 1 more Smart Citation